Grenzen der Automobilität? - Läpple, Dieter (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1997)
Mobility mostly is identified with the overcoming of spatial obstacles and in this sense equated with automobility. However on the level of society, the net result of the progress of automobile oriented traffic-systems is not a reductio of time but an extension of spatial structures and a reinforced segregation of urban functions. This leads to growing traffic and reinforced dependency on the possession of an automobile. The only limit to this traffic-system is ist own success, which leads to the destruction of social and ecological space. The author asks for a new conceptualization of space: space should no longer be regarded as an obstacle (in the sense of distance), which has tobe annihilated, but as a social potentiality (in the sense ofliving and working context), which has tobe reevaluated.